A description of the language experiences of English Second-Language students entering the academic discourse communities of Rhodes University - Reynolds, Judith Marsha (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1998)
This study is a description of the language experiences of English Second Language students in their first year at Rhodes University. It took place in the context of the changes that are currently occurring in higher education in South Africa in terms of student populations. More and more students are entering tertiary education institutions, including HWESUs, such as Rhodes University, who are considered non-traditional. These students typically have English as their second, or additional, language, and have not been adequately prepared for university study by their secondary education. This study describes the experiences of three such students in their first year at Rhodes University. Entry into a university is seen not just as acquiring knowledge, but as entering, or attempting to enter, a new culture. It is recognised that all students enter universities with other cultures or literacies already in place. In the case of non-traditional students tbese other literacies are usually at some distance from those of the university. The work of James Gee (1990) is particularly useful in understanding this process of adjusting to the demands of university study and the effect that previous experiences have on this process. This study is an attempt to discover and describe the literacies that these three students brought with them to university and the effect these literacies had on their attempts to enter academic discourse communities of the university. An ethnographic research method was adopted in order to do this. The study is also an attempt to evaluate, from the perspective of the three students, the appropriacy of the various changes that Rhodes University has made since the numbers of non-traditional students has started to increase.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Ability testing